Arsenic exposure in northern Mexican women - Brenda Gamboa-Loira; Mariano E Cebrián; Lizbeth López-Carrillo (Instituto Nacional de Salud Pública, 2020)
Objective. To describe interindividual metabolism variations and sociodemographic characteristics associated to urinary arsenic, and to estimate the arsenic contamination in water from urinary total arsenic (TAs). Materials and methods. Women (n=1 028) from northern Mexico were interviewed about their sociodemographic characteristics and their urinary concentrations of arsenic species were measured by liquid chromatography. Inorganic arsenic (iAs) in water was estimated from urinary TAs. Results. Women were 20-88 years old. TAs in urine ranged from p10=3.41 to p90=56.93 μg/L; 74% of women had levels >6.4 μg/L. iAs in water varied from p10=3.04 to p90=202.12 μg/L; 65% of women had concentrations >10 μg/L, and 41%, concentrations >25 μg/L. Large variations in iAs metabolism were observed. TAs was significantly negatively associated with age and schooling, and positively with the state of residence. Conclusion. Exposure to iAs is an environmental problem in Mexico. Individual variations in metabolism are a challenge to design prevention and control programs.